Neal Stephenson and the Franchise-State: Questioning Preconceptions of Nation-States and Borders from a Legal Perspective - Steve Crawford (Janeway JS, 2018)
Migration and borders have been placed at the centre of recent political movements. Populist right-wing candidates in countries throughout Europe and in the US have built momentum by demonising migrants and calling for the institution of strong borders. Much of this political rhetoric is driven by agendas of cultural preservation and domestic prioritising of so called indigenous national populations. The maintenance and preservation of the home country is privileged above any consideration of wider humanity. The concept of the nation-state, with its inherent notion of borders, seem embedded in these ideas. By looking beyond the conventional arena of state theorising – law, politics, international relations etc. – can a new perspective be found to move past this impasse? Using Neal Stephenson's novel Snow Crash this article seeks to find a new conceptual position from which to consider prevailing narratives surrounding borders and migration. Attempting to conceive of an alternative way to frame questions stemming from considerations of national identity and geographic space, especially from the perspective of the central legal document to these processes, the constitution.